Pengaruh Persepsi dan Partisipasi dalam Manajemen Rantai Pasok Berkelanjutan: Studi pada Pengguna Smartphone di Kota Semarang - Haunan Damar (Jurnal Manajemen Dayasaing, 2023)
This study aims to determine consumer perception and participation in sustainable supply chain management of smartphone products in the city of Semarang. The study was carried out by examining consumer perception and participation in sustainable supply chain management on purchase intention. This study also examines whether purchase intention mediates consumers' willingness to pay more. The data collection method used was survey questionnaire, the sampling method used was purposive sampling with an unlimited number of population. The data that has been collected is processed using SmartPLS to determine the direct and indirect effects of purchase intention on willingness to pay more. The result of this study indicates that there is a direct effect of purchase intention on willingness to pay more. The results also show that there is an influence of perception and participation in sustainable supply chain management on purchase intention and willingness to pay more.